Effects of Seed Treatments Using Extracts of Oxalis barrelieri L. and Cymbopogon citratus Stapf, Coupled with NaCl Sorting on Seed Health, Germination, Emergence and Seedlings Vigor, of Rice (Oryzae sativa L.) Seeds - Julienne, Nguefack; Romain, Fouelefack François; Blaise, Dongmo Lekagne Joseph; Rene, Azah Udom; Albert, Dongmo Nanfack; Molière, Djoufack Metis; Ephrem, Nkengfack Augustin (Cutting-edge Research in Agricultural Sciences Vol. 6, 2021)
The extracts of Oxalis barrelieri and Cymbopogon citratus were tested for their antifungal activity against Bipolaris oryzae and Fusarium moniliforme, and use as seed treatment coupled with NaCl treatment to improve the seed germination and the seedlings vigor of treated rice seeds. The significance of the inhibitory activity of the plant extracts against B. oryzae and F. moniliforme was type of extract and concentration dependent. The ethanolic extract of C. citratus at 10000 ppm, showed the highest inhibitory effect, with 58.51% and 55.9% growth inhibition of F. moniliforme and B. oryzae, respectively. The rice seeds sorted in 20% NaCl solution had a greater mass (quantify), a germination percentage of 13% higher as compared to seeds sorted in with water and 20% higher than that of unsorted seeds. A moderate positive and significant linear relationship (Rho (78) = 0.427 **, p <0.01) was shown between weight and germination of rice seeds. The ethanol extracts of O. barrelieri and C. citratus stimulated rice seed germination at a comparable degree; 15- 22% from the top of paper method and 11-16% from sand method in green house trials. Rice seed treatments at 1% concentration, exhibited the best germination/emergence and reduced the seed infestation of B. oryzae and F. moniliforme by 25.25% and 9.83%, respectively. Stressed seeds treated with plant extracts showed less pronounced decrease (5 %) in germination compared to untreated stressed seed (26%). The germination and the emergence were each negatively correlated with both the seed infestation of B. oryzae and F. moniliforme; only the correlation between the germination and the infestation of F. moniliforme (r (54) = -0.441**, p < 0.01) and that between the emergence and the infestation of F. moniliforme (r (54) = -0.426**, p < 0.01) were moderately and statistically significant. Sorting of rice seeds with 20% NaCl and/or treatment with 1% ethanol extracts of Oxalis barrelieri and Cymbopogon citratus showed potential green alternative to synthetic fungicides for the control of rice seed-borne infestation, improvement of seedling vigor and increase of seed germination and emergence for the effective field establishment of seedlings .